PELATIHAN PENGOLAHAN LIMBAH SAYUR SEBAGAI PAKAN ITIK DI KECAMATAN TERNATE SELATAN - Sri Utami; Emy Saelan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
The Mandiri Community Partnership Program (PKM) “Training on Vegetable Waste Treatment as Duck Feed in South Ternate District” will be conducted with the partner farmer groups of Buku Sasa Mandiri cand find out about processing vegetable waste duck feed with nutritional content according to the needs of ducks based on the maintenance. The PKM Mandiri Community Partnership Program is carried out with the objectives of (1) Breeders can utilize vegetable waste as duck feed which is widely available in Ternate and its availability is very abundant; (2) Duck breeders do not depend on manufacturer’s feed which is very expensive; (3) Breeders have the ability to formulate vegetable waste as duck feed. The target achieved from the Independent Community Partnership Program (PKM) is that farmer can process vegetable waste that is a problem for the environment into animal feed, so as to reduce feed costs. The results from PKM Mandiri show that farmers can make processing of vegetable waste into duck feed physically and with fermentation techniques, so that partner groups do not depend on manufactured feed. The quality of the feed produced meets the standard needs of ducks, so that it can produce optimal growth an production.